Changes in Land Use in the Municipality of Cerkvenjak - Žiberna, Igor; Jambrošič, Klara; Pepevnik, Aleksandra; Bedök, Klemen (Journal for Geography, 2023)
The article presents changes in land use in the area of the municipality of Cerkvenjak, Slovenia, in the period 2000-2023. Changes in land use are shown as a function of some natural geographical factors (relief, topoclimatic characteristics…). The directions of changes in land use are also analyzed in relation to the process of extensification, i.e. changes of cultivated land to non-cultivated land. The changes in vineyard areas are specially analyzed. We also included in the analysis older georeferenced and digitized data from the Franciscan cadastre for the area of the present municipality of Cerkvenjak from 1824.